Performance evaluation of micro orc systems for power generation in nearly zero energy buildings (NZEB) - Shesho, Igor; Blazheska, Martina; Vasikj,Nebojsha; Tashevski, Done; Mojsovski, Filip (Faculty of mechanical engineering, University of Banja Luka, 2019)
According the Energy Performance of Buildings Directive it is required all new buildings to be nearly zero-energy by the end of 2020. Micro cogeneration systems are considered as one of the system solutions with the highest potential to enable nearly zero energy buildings (nZEB). In this paper is assessed the potential for application of Micro-Organic Rankine Cycle system for power generation in nZEB, where as a heat source is considered solar energy (solar thermal collectors) biomass (pellet boiler), which are also integrated part of the heating system and DHW. Analysis is performed in order to select optimal ORC working fluid for highest thermal efficiency. The solar thermal system, building, heating/cooling and DHW systems are modeled with Transient System Simulation Tool (TRNSYS) and for the meteorological data is used Typical Meteorological Year for Macedonia.
Keywords: Organic Rankine Cycle, nZEB, Renewable energy, solar collectors, biomass